Characterizing the gut microbiota in adults with bipolar disorder: a pilot study. (4th March 2021) - McIntyre, Roger S.; Subramaniapillai, Mehala; Shekotikhina, Margarita; Carmona, Nicole E.; Lee, Yena; Mansur, Rodrigo B.; Brietzke, Elisa; Fus, Dominika; Coles, Alexandria S.; Iacobucci, Michelle; Park, Caroline; Potts, Ryan; et al.
ABSTRACT: Background: Convergent evidence implicates gut microbiota in human health and disease. Hitherto, relatively few studies have evaluated the gut microbiota profile in individuals with bipolar disorder (BD) relative to healthy controls (HC). Methods: Fecal samples were collected from subjects (aged 18–65) meeting DSM-5-defined criteria for BD and age- and sex-matched HC without current or past history of mental or major medical disorders. Samples were sequenced using Illumina sequencing and association of specific taxa and co-occurrence of taxa with sample groups including the effect of diet was assessed using cluster analysis and analysis of communities of microorganisms (ANCOM). Nutritional composition was evaluated using the Dietary Questionnaire for Epidemiological Studies (DQES v2) Food Frequency Questionnaire. Results: Forty-six subjects were enrolled ( n =23 BD, n =23 HC). Cluster analyses did not identify any significant differences between BD and HC ( p =0.38). Lower microbiota diversity was observed among BD subjects relative to HC ( p =0.04). A greater abundance of a Clostridiaceae OTU was observed among BD subjects when compared to HC and of Collinsella among BD-II subjects relative to BD-I. Cluster analysis revealed that neither diagnosis ( p =0.38) nor diet ( p =0.43) had a significant effect on overall gut microbiota composition. Limitations: This study has a small sample size and insufficient control for some potential moderating factors (e.g. psychotropic medication and smoking). Conclusion: This study suggests that individuals with BD may have a distinct gut microbiota profile compared to healthy controls, with a greater abundance of Clostridiaceae and Collinsella . These findings need to be replicated in future studies with larger sample sizes.